Reflections from a reference service: proposals for improving the attention given to citizens in archives - Hernández Luis, José Luis (Revista General de Información y Documentación, 2016)
This paper proposes some advances in legislation, methods and means in order to improve the attention given to users in archives. With this in mind, and based on our experience, the current theory and practice are discussed as we consider mainly the problems of state historical archives. The results show that implementing legislation of state archives, taking advantage of new technologies for standardization and simplification of procedures, counting on sufficient means, in addition to evaluation and user training, are all required.